United in diversity? comparing social models in Europe and America - Alber, Jens, 1947-; Gilbert, Neil, 1940-; University of Maryland (College Park, Md.). Center for International Policy Exchanges (Oxford : Oxford University Press, 2010)
This book systematically analyzes how much European countries and the U.S. have in common and how much variation we find within the enlarged E.U. in central spheres of socio-economic and political life.
Published in association with The Center for International Policy Exchanges.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Europe -- Social policy; United States -- Social policy; Public welfare -- Europe; Public welfare -- United States